Toward an understanding of dominated bidding in a Vickrey auction experiment - Shigehiro Serizawa; Natsumi Shimada; Tiffany Tsz Kwan Tse (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This study explores two key factors influencing subjects' deviation from domi- nant bidding in Vickrey auction experiments. The first factor examines subjects' understanding of strategy-proofness (SP), while the second focuses on "human interaction" which includes social preferences (spite and altruism), responses to strategic uncertainty, and tacit collusion. To analyze the effect of understanding SP, we quiz subjects before an experimental Vickrey auction and examine whether their bidding behavior changes if one of the quizzes includes hints about SP. We design the quiz carefully, incorporating implicit hints about SP and ensuring the avoidance of explicit demands or advice to mitigate experimenter demand effects. However, completing the quiz enables the subjects to understand SP themselves. To analyze the effects of human interaction, we examine whether subjects' bidding behavior changes if they compete against robots instead of human rivals in the auctions. We design 2 2 treatments by varying the type of quiz (with or without hints about SP) and the nature of the rivals (humans or robots). We found that the quiz with hints about SP increases dominant bidding. The nature of rivals also influences the bidding behavior; nonetheless, its impact is not as robust as that of SP hints. Thus, the main factor causing dominated bidding in Vickrey auction experiments is not human interaction but a lack of understanding of SP.
Keywords: D44; D82; D61; 330; Market design; Strategy-proofness; Vickrey auction; Hints; Human interaction; Human vs robot rivals